Plasma Diagnostic by Probes - Tichy, M. chemist Professor of Tomsk Polytechnic University, Doctor of physical and mathematical sciences 1947- (Изд-во ТПУ, 2015)
Scientific basis of low-temperature plasma probe diagnostics is described in the textbook. Overview of probe methods of plasma diagnostics and a wide range of issues in their practical use is shown. Theoretical study of these methods, detailed description of the design features and the necessary formulas are given. Estimates of possible errors are made, a variety of tests are described. Using the Langmuir probe allows to obtain reliable data on the concentration of free electrons with high spatial and temporal resolution and to obtain estimates of the ratio of the concentrations of negative ions and free electrons in the plasma.Designed for students studying in the direction 140800 Nuclear physics and technology)).